PENDAMPINGAN UMKM DI DESA BANYUBIRU DALAM PEMANFAATAN TEKNOLOGI DIGITAL - Aryandha, Pradita Nindya; Putranti, Latifah; Herdiany, Hapsari Dyah; Nugraha, Aditya; Tabun, Putri Sriariani (Universitas katolik Musi Charitas, 2024)
This community service program is an initiative that supports the development of MSMEs in Banyubiru Village. The goal is to help MSMEs adapt and respond to changing conditions through gradual assistance. It is hoped that this can increase sales and expand their business development sustainably. MSMEs have a vital role in the Indonesian economy, including in Banyubiru Village, Dukun District, Magelang Regency. The community service method is carried out in three stages, namely preparation, implementation, and evaluation. The preparation stage involves observation and identification of problems, while the implementation stage includes socialization, creation of social media, marketplace training, input of business locations to GoogleMaps, and promotion through AdSense. Evaluation is carried out to measure the effectiveness of the program. The results show high enthusiasm from MSMEs and an increase in the use of technology to increase sales and visibility of their products.